Heterogeneity within the Asian American community - Sadler, Georgia Robins (BioMed Central, 2003)
BACKGROUND: Educational interventions are grounded on scientific data and assumptions about the community to be served. While the Pan Asian community is composed of multiple, ethnic subgroups, it is often treated as a single group for which one health promotion program will be applicable for all of its cultural subgroups. Compounding this stereotypical view of the Pan Asian community, there is sparse data about the cultural subgroups' similarities and dissimilarities. The Asian Grocery Store based cancer education program evaluation data provided an opportunity to compare data collected under identical circumstances from members of six Asian American cultural groups. METHODS: A convenience sample of 1,202 Asian American women evaluated the cultural alignment of a cancer education program, completing baseline and follow-up surveys that included questions about their breast cancer knowledge, attitudes, and screening behaviors. Participants took part in a brief education program that facilitated adherence to recommended screening guidelines. RESULTS: Unique recruitment methods were needed to attract participants from each ethnic group. Impressions gained from the aggregate data revealed different insights than the disaggregate data. Statistically significant variations existed among the subgroups' breast cancer knowledge, attitudes, and screening behaviors that could contribute to health disparities among the subgroups and within the aggregate Pan Asian community. CONCLUSION: Health promotion efforts of providers, educators, and policy makers can be enhanced if cultural differences are identified and taken into account when developing strategies to reduce health disparities and promote health equity.